Can Surgery be Avoided After Preoperative Chemoradiation for Rectal Cancer in the Era of Organ Preservation? Current Review of Literature. (October 2015) - Chawla, Sheema; Katz, Alan W.; Rauh, Stephen M.; Monson, John R. T.
Abstract : Approximately 10% to 25% of patients have a pathologic complete response after neoadjuvant chemoradiation. There is a compelling argument for attempting to avoid surgery in carefully selected groups of patients. Although nerve-preserving surgical techniques are now standard, the rates of urinary and sexual dysfunction are significant. Also, although sphincter function and quality of life among patients undergoing an ultra-low anterior resection is acceptable, results are poorer than expected and may be disabling. Trials of omission of surgery for selected patients with complete response after preoperative chemoradiation, otherwise known as "Watch and Wait, " have shown favorable long-term results. We review the current literature on accepted standards of care and identify areas of controversy and important ongoing clinical studies aiming to resolve these issues.